Ambulatory Endoscopic Thyroidectomy via a Chest-Breast Approach Has an Acceptable Safety Profile for Thyroid Nodule - Zhang, Zeyu; Xia, Fada; Li, Xinying (Frontiers in Endocrinology, 2021)
Introduction: With the growing esthetic requirements, endoscopic thyroidectomy develops rapidly and is widely accepted by practitioners and patients to avoid the neck scar caused by open thyroidectomy. Although ambulatory open thyroidectomy is adopted by multiple medical centers, the safety and potential of ambulatory endoscopic thyroidectomy via a chest-breast approach (ETCBA) is poorly investigated. Material and methods: Patients with thyroid nodules who received conventional or ambulatory ETCBA at Xiangya hospital, Central South University from January 2017 to June 2020 were retrospectively included. The incidence of postoperative complications, 30-days readmission rate, financial cost, duration of hospitalization, mental heath were mainly investigated. Results: A total of 260 patients were included with 206 (79.2%) suffering from thyroid carcinoma, while 159 of 260 received ambulatory ETCBA. There was no statistically significant difference in the incidence of postoperative complications (P=0.249) or 30-days readmission rate (P=1.000). In addition, The mean economic cost of the ambulatory group had a 29.5% reduction compared with the conventional group (P<0.001). Meanwhile, the duration of hospitalization of the ambulatory group was also significantly shorter than the conventional group (P<0.001). Patients received ambulatory ETCBA showed a higher level of anxiety (P=0.041) and stress (P=0.016). Subgroup analyses showed consistent results among patients with thyroid cancer with a 12.9% higher complication incidence than the conventional ETCBA (P=0.068). Conclusion: Ambulatory ETCBA is as safe as conventional ETCBA for selective patients with thyroid nodules or thyroid cancer, however with significant economic benefits and shorter duration of hospitalization. Extra attention should be paid to manage the anxiety and stress of patients who received ambulatory ETCBA.